2009
DOI: 10.1111/j.1601-0825.2009.01570.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of chlorhexidine substantivity on salivary flora by epifluorescence microscopy

Abstract: Epifluorescence microscopy permits evaluating the antimicrobial activity of CHX on the salivary flora in real-time. Fluorescence assays could be particularly useful to analyse simultaneously the effect of antimicrobials that alter the cytoplasmic membrane integrity on different oral ecosystems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
42
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 36 publications
8
42
0
Order By: Relevance
“…It has been stated that this specific solution has a general tendency to artificially increase the levels of non-vital bacteria 28 with regard to the plate cultures and the plate efficiency. In a previous study, 12 it has been shown a correlation between the immediate effect and the plate cultures; however, this correlation was lost as time passed, with the effect of CHX being overestimated by plate cultures, 12 indicating that the bacterial vitality may be underestimated with plate cultures or overestimated with fluorescence techniques, which is in contra to what has been recently stated. 28 In this same way, Hannig et al 29 showed that live/dead techniques were valid when assessing bacterial vitality after the use of antiseptic agents, being the combination of Syto 9/propidium iodide a reliable tool when assessing bacterial vitality in a multispecies biofilm.…”
Section: Methodological Approachmentioning
confidence: 68%
See 4 more Smart Citations
“…It has been stated that this specific solution has a general tendency to artificially increase the levels of non-vital bacteria 28 with regard to the plate cultures and the plate efficiency. In a previous study, 12 it has been shown a correlation between the immediate effect and the plate cultures; however, this correlation was lost as time passed, with the effect of CHX being overestimated by plate cultures, 12 indicating that the bacterial vitality may be underestimated with plate cultures or overestimated with fluorescence techniques, which is in contra to what has been recently stated. 28 In this same way, Hannig et al 29 showed that live/dead techniques were valid when assessing bacterial vitality after the use of antiseptic agents, being the combination of Syto 9/propidium iodide a reliable tool when assessing bacterial vitality in a multispecies biofilm.…”
Section: Methodological Approachmentioning
confidence: 68%
“…Since epifluorescence microscopy has been considered an observer-dependent technique, 12 it is important to determine the intra-and inter-observer correlations. In the present series, the ICC mean values were !0.85.…”
Section: Methodological Approachmentioning
confidence: 99%
See 3 more Smart Citations